MALWARE ANALYSIS NETWORK IN UZBEKISTAN (MIT) - Husanboy Shoraimov Uktamboyevich (Journals Park Publishing, 2022)
Malware is one of the problems really existing in the modern post-industrial society. Hackers continuously develop novel techniques to intrude into computer systems for various reasons, so many security researchers should analyze and track new malicious program to protect sensitive information for the computer system. In this paper, we integrate the Interval Type-2 Fuzzy Logic System (IT2FLS) with malware behavioral analysis: Malware Analysis Network in Uzbekistan (MAN in Uzbekistan, MiT). The core techniques of MiT are as follows: (1) automatically collect the logs the difference operation system to extract unknown behavior information.
Keywords: Type-2 Fuzzy Sets; Interval Type-2 Fuzzy Logic System; Web Ontology Language